Effect of steaming temperature on microstructure and mechanical, hygric, and thermal properties of binderless rape straw fiberboards. (September 2022) - Jerman, Miloš; Böhm, Martin; Dušek, Jaroslav; Černý, Robert
Abstract: Rape straw as a waste product of the oilseed industry is available abundantly in the European Union. In this paper, the utilization of rape straw-based fibers for the preparation of binderless thermal insulation materials is investigated. The effect of steaming temperature, which can be considered as one of the most important parameters of the production process, on microstructure and mechanical, hygric and thermal properties of the insulation boards is analyzed. The experimental results show that the designed binderless rape straw fiberboards achieve the most suitable combinations of mechanical, hygric and thermal properties for the steaming temperatures of 180 °C and higher, which indicates 180 °C as the most promising solution. Highlights: Binderless rape straw fiberboards with a bulk density of 100 kg/m 3 were designed. The effect of steaming temperature is analyzed. Thickness swelling decreased substantially with increasing steaming temperature. The most suitable properties achieved fiberboards produced at 180 °C and 200 °C. The thermal conductivity was within the range of 0.045–0.052 W/mK.